The Embedding of Islamic Education Values in the Development of Student Characters at al-Ikhlas Islamic High School in Ujung-Bone - Siddik, Hasbi (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2018)
This article starts from three main problems: embedding character values at al-Ikhlas Madrasah Aliyah of Ujung-Bone, encountering the opportunities and challenges during the process. This qualitative research is based on phenomena that occur in the field. The approaches used are pedagogical analysis, normative and juridical approach. The results explain, that the character security processes carried out by teachers are to be honest, responsible, nationalism, social care, affection, tolerance, discipline, and creative in developing their potential. They attempt to guard the educational process of cultivating character by conducting behavioral supervision of students. Embedding students’ character can motivate and tell the story of successful people. The strong desire of stakeholders to foster and advance Madrasah is in accordance with the expectations of the founders. Although, there are limited standard specifications of educational staffs, the values of Islamic education are very important in the joints of life. Therefore, Islamic education inherits human values to students, encourages students, not only to equip themselves for individual interests, but also to devote themselves to the community.